Implementation of Sex Education in Indonesia: A “Sine Qua Non” in Taboo - Situmorang, Dominikus David Biondi (Buletin Psikologi, 2024)
There are significant differences between the methods used in Western and Eastern culture to discuss sex. Any topic related to sex in Eastern culture, specifically Indonesia, is often considered taboo compared to Western culture. This is due to the strong cultural and religious values prevalent in Eastern societies, making discussions about sex feel impolite and inappropriate. Therefore, this study aimed to explore the importance of sex education as a “sine qua non” in Indonesia and the consequences of treating sex education as a taboo. The exploration process would examine the role of parents, teachers, counselors, psychologists, and the community in sex education, new sex education policies, along with recommendations, implications, and directions for future investigations.